Analasis Pajak Bumi dan Bangunan (PBB): Konsep, Implementasi, dan Peranannya dalam Penerimaan Daerah - Anis Kartika Hutabarat; Aril Saputra Sitorus; Kiki Eka Sari (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Land and Building Tax (PBB) is one of the important sources of income for local governments in Indonesia. This tax is imposed on objects in the form of land and buildings owned, controlled, or utilized by taxpayers. This article discusses the basic concept of PBB, legal basis, mechanism for determining the Taxable Object Sales Value (NJOP), and the role of PBB in supporting regional development financing. In addition, this article also examines the challenges and opportunities in optimizing PBB collection. The results of the study indicate that increasing the accuracy of NJOP determination and strengthening the tax administration system can significantly increase regional revenues. Therefore, synergy between the central and regional governments and active community participation are needed to optimize the potential of PBB as a source of regional income.